Real-world evidence data on the monoclonal antibody erenumab in migraine prevention: perspectives of treating physicians in Germany - Andreas Straube (BMC, 2021)
Abstract Background Erenumab, the first-in-class fully human monoclonal antibody targeting the calcitonin gene-related peptide receptor, was shown to be efficacious and safe for the prophylactic treatment of migraine in adults in randomized clinical trials. Large-scale, real-world evidence in multi-centre settings is still needed to confirm these results. Erenumab patient profiles outside clinical trials and physicians’ treatment patterns, as well as data from patients treated in Germany, a severely impacted population, are not published yet. Methods TELESCOPE was a multi-centre survey gathering real-world data from 45 German headache centres between July 2019 and December 2019. The project consisted of two parts. In the first part, treating physicians shared their experiences on current erenumab treatment with regard to patient profiles, treatment patterns and treatment responses. In the second part, a retrospective chart review was conducted of 542 migraine patients treated with erenumab for at least three months. Treatment responses focused on various aspects of patients’ quality of life. Results The analysis of 542 patients’ charts revealed that three-month treatment with erenumab significantly reduced monthly headaches, migraine and acute medication days. Furthermore, headache intensity and frequency were reduced in over 75 % and accompanying aura in 35 % of patients. The clinical global impression scale revealed a general improvement in 91 % of patients. According to the treating physicians’ professional judgement, 83 % of patients responded to erenumab and 80 % were satisfied with the treatment. Physicians evaluated restricted quality of life, the number of monthly migraine days and previous, prophylactic treatments as the main components of the current patient profile for monoclonal antibody recipients. Based on the assessment of physicians, erenumab reduced migraine symptoms in 65 % and increased quality of life in more than 75 % of their patients. Conclusions TELESCOPE confirms positive treatment responses with erenumab shown in clinical trials in a real-world multi-centre setting. The results show consistently positive experiences of physicians utilizing erenumab in clinical practice and underline that therapy with this monoclonal antibody is effective in migraine patients, particular in those, who have failed several prophylactic therapies.